(untitled) (Transport systems and technologies, 2020)
The determination of the dynamic loading of a container of 1СС standard size, placed on a roll-trailer during transportation by a railway ferry, has been carried out. It was found that in the absence of movements of the roller trailer relative to the deck and the container relative to the roller trailer (I diagram), the maximum accelerations that act on the container are 0.33g. In the absence of movements of the roller trailer relative to the deck and the presence of movements of the container on the roller trailer (II diagram), the maximum accelerations that act on the container are equal to 0.43g. The resulting accelerations were taken into account when studying the stability of a container on a roll-trailer during transportation by a rail ferry. It has been established that the stability of a container on a roller trailer, taking into account the typical interaction scheme (fitting stop - fitting), for the first scheme is provided at roll angles up to 270, and for the second scheme - up to 250. The natural frequencies of vibrations of a container placed on a roll-trailer during transportation by sea have been determined. The research carried out contributes to ensuring the safety of container transportation by rail ferries by sea, as well as increasing the efficiency of the functioning of combined transport in international traffic.